Concerted pulsatile and graded neural dynamics enables efficient chemotaxis in C. elegans - Eyal Itskovits (Nature Portfolio, 2018)
Finding one’s way to a food source along a complex gradient is central to survival for many animals. Here, the authors report that in C. elegans, the distinct response dynamics of two sensory neurons to odor gradients can support a navigation model more efficient than the biased-random walk.